Strengthening regional investment facilitation rulemaking in Asia: The why and the how - Manjiao Chi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Asian countries should enhance regional investment facilitation rulemaking despite their diverse level of development. This Perspective discusses the various courses of action Asian countries could take to improve regional investment facilitation rulemaking and the major challenges they face.
Keywords: 330